Dynamic analysis of the high-power factor three-phase AC to DC converter using current injection hybrid resonant Technique - Rahimi Baharom; Mohammad Nawawi Seroji (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the dynamic analysis of the high-power factor three-phase ac to dc converter using current injection hybrid resonant technique in order to investigate the characteristics of the output voltage, line current, DC-link voltage and the resonant current of the proposed converter. The dynamic analysis have been developed based on a separate analysis of the rectifier line-frequency operation and at the resonant circuit high-frequency. Converter circuit analysis have been performed based on the operation at the fundamental frequency. The power balance relation method has been included in order to match the line frequency equation with the high frequency resonant stage equation. This analysis can be envisaged to be the heart of the small-signal model to design the output voltage regulation and maintain a high-power factor input line current of the proposed converter.